(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon the Master of Messengers and the Seal of the Prophets, Muhammad.Al-Amin, and his family and companions until the Day of Judgment.There is no doubt that Arabic has received great care and effort, the source of which is the study of the Noble Qur’an.And an attempt to explain its miracles, the nature of its systems and its structure, and to understand its meanings and understandings.Hundreds of books were contributed by ancient and modern linguists, some of which have struggled for days.Then a new phase began in the study of the language, which was approved by the Orientalists, and they adoptedIn it, the study of the Arabic language within the group of Semitic languages and the balance between them.The truth is that studying language and its philosophy is not an easy matter.Kindness and I want to explain the linguistic system in which Arabic is organized, it must face a number ofObstacles and difficulties that can only be overcome with farsightedness and deep thinking.